DIPLOMASI EKONOMI INDONESIA DALAM MENINGKATKAN EKSPOR TUNA KE JEPANG PERIODE 2018 - 2022 - Annisa Azzahra, (2024)
This research aims to discuss the economic diplomacy carried out by Indonesia in its efforts to increase tuna exports to Japan using economic diplomacy theory, the concept of tariff barriers and non-tariff barriers. The method used in this research is descriptive qualitative using primary data sources and secondary data. In this research, the author used four stages of data analysis according to Miles & Huberman, namely data collection, data reduction, data presentation and also verification with data triangulation. The final results in this research shows that the economic diplomacy carried out by Indonesia is limited. The economic diplomacy carried out by Indonesia is quite diverse, but not all of it has had a good impact. In this research, it was found that the Economic Salesmanship and Image Building stages could have a positive impact on the increase, but the implementation of the Networking and Regulation Management stages still had little impact on the increase in exports. However, overall economic diplomacy can help increase tuna exports to Japan.